PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SENI RUPA SISWA KELAS XI SEKOLAH MENENGAH ATAS NEGERI 1 DUMAI - Tedi Hilal Najmi; Ramalis Hakim (Serupa The Journal of Art Education, 2020)
This study aims to determiine the difference in visual art lerning outcome of students of class XI taugh used the Project Based Learning (PBL) learning model with the results of student art learning taught using conventional learning methods at SMAN 1 Dumai. This type of research is quasy experiment. The study population was student of class XI of SMA Negeri 1 Dumai. The sampling technique was purposive sampling with a sample of class XI IPA 2 of the control class of 35 students and the experimental class of 30 students. The instruments of the reserch we pretest, post test and observation sheet. Data analysis technique is descrptive analys and inductive analys that is normality tes, homogeneous tes, variation and t test. The results showed that the aveage value of the experimentaal clas wav 80.13 and the control class was 74.80. From the hypothesis test results obtained t hit 2.3039 and t tab 1.9971 with α 0.05. So t hit> t tab, then Ho is rejected, so there are difference in leaning outcome in class XI students taugh used the Project Based Learning (PBL) learning model with student' art learning outcomes taugh used konventional leaning methods at SMAN 1 Dumai .. Findings research shows that learning outcomes in classes applying Project Based Learning (PBL) learning models are higher than in classes using conventional methods.Keywords: Project Based Learning Model Learning, Learning Outcomes.